Retrovisions : Reinventing the Past in Film and Fiction - Cartmell, Deborah; Hunter, I. Q., 1964-; Whelehan, Imelda, 1960- (Film/fiction, 2001)
"This book looks at the ways in which films and texts re-imagine the past, to investigate what this may reveal about our contemporary culture and society. Looking at a broad range of films and books that attempt to represent the past and placing them in their own historical context, the authors examine how different eras are represented, what they have come to signify, and what this reveals about the society that reimagines them. Using a wide range of examples, contributors consider nostalgia, intertextuality, pastiche, and contemporary culture." --